Grain yield performance and stability of rice variety mixtures and their component cultivars in monoculture - Meher, J; Das, S R (ORYZA-An International Journal of Rice, 2018)
It’s usually presumed that variety mixtures perform better and are more stable than their component cultivarsÂ under diverse growing environments. Therefore, the grain yield performance and stability of six early riceÂ varieties and their fifteen bi-varietal mixtures in all combination were assessed over four growing seasons in aÂ tropical coastal Odisha climate. The mixture constituted equal proportion of both the varieties and were atÂ same overall density as like the cultivar in monoculture. The grain yield stability based on regression model of Eberhart and Russel (1966) indicate that all the varieties including mixtures were stable in the trial environmentsÂ as deviation from regressions were not significantly different from zero. Based on mean grain yield over environments Annapurna followed by Keshari and Parijat were the top yielder among the cultivars; while theÂ mixture Annapurna+Annada produced highest yield followed by Annapurna+Parijat and Annapurna+Keshari.Â Further, mixture Annapurna+Keshari would perform well in favourable environment as indicated from higherÂ grain yield from the grand mean with significantly higher bi value ; whereas cv Suphala would perform betterÂ in poorer environment, which had lesser yield from the grand mean with significantly lower bi value from unity.Â Rabi 2006 was the most productive, whereas kharif 2006 was the most stressful environment with overall highÂ and low mean grain yield of entries respectively.Â